2018
DOI: 10.1016/j.jid.2017.08.048
|View full text |Cite
|
Sign up to set email alerts
|

Microbe-Dependent Induction of IL-9 by CLA+ T Cells in Psoriasis and Relationship with IL-17A

Abstract: IL-9 is present in psoriatic lesions and is produced by lymphocytes. However, it is not known whether this cytokine is induced by relevant pathogenic triggers of psoriasis, such as Streptococcus pyogenes. Here we addressed the production of IL-9 in response to various pathogens in a psoriatic ex vivo model. Extracts of S. pyogenes and Candida albicans triggered the production of IL-9 and also IL-17A and IFN-γ. This induction was dependent on the interaction between CLA T cells and epidermal cells. Neutralizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…Our studies have shown that, in CPP patients without clinical evidence of S. pyogenes infection, only CLA + T cells respond to this microbe in comparison to healthy controls. This observation indicates that psoriasis patients present an adaptive immune response to S. pyogenes through IL-17A, IL-17F, IL-9, and IFN-γ production ( 20 , 21 , 24 ) and suggests that S. pyogenes modulates the response of the CLA + T cells that maintain psoriatic lesions, i.e., pyogenes infection has been describe to participate in CPP infection, since higher levels of IgG against S. pyogenes proteins are detected in psoriasis patients in comparison to healthy controls ( 25 ). Some studies have reported the presence of the genera Streptococcus in normal and psoriatic skin ( 26 ) and the isolation of S. pyogenes in the skin of GP patients ( 4 ), probably leading to cutaneous immunization and a CLA + T cell-restricted response in psoriasis.…”
Section: Cla + T Cell Activation By S Pmentioning
confidence: 95%
See 3 more Smart Citations
“…Our studies have shown that, in CPP patients without clinical evidence of S. pyogenes infection, only CLA + T cells respond to this microbe in comparison to healthy controls. This observation indicates that psoriasis patients present an adaptive immune response to S. pyogenes through IL-17A, IL-17F, IL-9, and IFN-γ production ( 20 , 21 , 24 ) and suggests that S. pyogenes modulates the response of the CLA + T cells that maintain psoriatic lesions, i.e., pyogenes infection has been describe to participate in CPP infection, since higher levels of IgG against S. pyogenes proteins are detected in psoriasis patients in comparison to healthy controls ( 25 ). Some studies have reported the presence of the genera Streptococcus in normal and psoriatic skin ( 26 ) and the isolation of S. pyogenes in the skin of GP patients ( 4 ), probably leading to cutaneous immunization and a CLA + T cell-restricted response in psoriasis.…”
Section: Cla + T Cell Activation By S Pmentioning
confidence: 95%
“…IL-9 production is dependent on MHC class I and class II presentation, and it preferentially prolongs CLA + T cell survival. Higher amounts of IL-9 were detected in psoriasis patients than in healthy controls, but no differences were observed between GP and CPP patients ( 24 ). IL-9 has been associated with increased IL-17A production in an animal model of psoriasis ( 23 ).…”
Section: Cla + T Cell Activation By S Pmentioning
confidence: 96%
See 2 more Smart Citations
“…Variations in the number and phenotype of circulating CLA þ T cells are closely related to improved clinical outcome of patients with psoriasis (Thorleifsdottir et al, 2012). Our group has established a psoriasis ex vivo model based on the coculture of circulant CLA þ or CLA À T cells and autologous epidermal cells, isolated from skin biopsies from patients with lesional psoriasis, which are then activated by a S. pyogenes extract (SE), leading to specific IL-17 response in CLA þ but not CLA À T-cells cultures (Ferran et al, 2013;Ruiz-Romeu et al, 2018.…”
Section: Introductionmentioning
confidence: 99%